TOPICAL ISSUES OF ASSESSING THE PROPORTIONALITY OF ADMINISTRATION IN THE CONTEXT OF ADMINISTRATIVE APPEAL AND JUDICIAL REVIEW - Aleksanyan, Kristine (State and Law, 2022)
The work is devoted to the study of topical issues of assessing the proportionality of administration in the context of administrative appeal and judicial review. The functional aspect of the separation of powers requires that, when considering the proportionality of the exercise of administrative discretion, the court should not assume the functions of an administrative body, and its assessments should not interfere with the discretionary powers of an administrative body in unnecessary way, thereby eliminating the necessary boundary between justice and executive power. In this regard, it was justified in the work that when determining the proportionality of administration, the court should try to refrain from situations of unintentional replacement of an administrative body, which can be defined as reasonable respect for the independence of administrative bodies. At the same time, as a result of a comprehensive study of the concept of judicial respect, the circumstances that determine the degree of its manifestation were also presented.
Keywords: proportionality; administrative discretion; judicial review; judicial deference; institutional competence; proportional measure